2020
DOI: 10.1186/s10194-020-01203-5
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent brain structural and functional alterations in patients with migraine without aura: an fMRI study

Abstract: Objectives To explore the possible concurrent brain functional and structural alterations in patients with migraine without aura (MwoA) patients compared to healthy subjects (HS). Methods Seventy-two MwoA patients and forty-six HS were recruited. 3D-T1 and resting state fMRI data were collected during the interictal period for MwoA and HS. Voxel-based morphometry (VBM) for structure analysis and regional homogeneity (Reho) for fMRI analysis were ap… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 55 publications
1
21
0
Order By: Relevance
“…A study performed by Liang, F research showed the regional homogeneity change in migraine without aura patients using fMRI. 45 Linde K from the Technical University Munich had the highest number of co-citations. Moreover, Liu L, Li B, Xu XB, and Qu ZY were newly, but highly published authors in acupuncture on migraine research in recent years.…”
Section: Discussionmentioning
confidence: 96%
“…A study performed by Liang, F research showed the regional homogeneity change in migraine without aura patients using fMRI. 45 Linde K from the Technical University Munich had the highest number of co-citations. Moreover, Liu L, Li B, Xu XB, and Qu ZY were newly, but highly published authors in acupuncture on migraine research in recent years.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, many neuroimaging studies of migraine have focused solely on changes in brain structure or functional architecture ( Schwedt et al, 2015 ; Jia and Yu, 2017 ; Yu et al, 2021 ; Zhang et al, 2021b ). A more vital issue that has not been researched is whether and how the observed structural alterations are associated with functional deficits in migraine ( Li et al, 2020 ). Therefore, investigating both structural and functional changes in one sample can clarify the neural mechanisms of MM and guide the choice of treatment options.…”
Section: Introductionmentioning
confidence: 99%
“…Resting-state functional MRI is an imaging technique with great promise in examining coordinated activity between different brain regions, in the absence of any stimulation or tasks [ 5 ]. Utilizing this approach, multiple brain structures involved in the processing of pain, such as the hypothalamus, periaqueductal gray matter, hippocampus, amygdala, insula, basal ganglia, thalamus, sensorimotor and visual cortex, have been revealed to present atypical functional connectivity (FC) in migraine patients during the interictal phase [ 6 , 7 , 8 , 9 ]. Furthermore, several imaging studies on migraines have reported disrupted connectivity within or between resting-state networks, including the salience network, frontoparietal network, and default mode network (DMN) [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%